Evaluating the Impact of Saudi Vision 2030 on Healthcare Investment: A Comprehensive Review of Progress and Future Directions - Alfahad , Ali Hamdan; Alabbas, Yuosef Salem; ALabbas, Hussain Salem M; Abukhashbah, Thamer Hassan; Alabdali , Abdulmeen Abdullah; Alfatieh, Qublan Mohammad Hammad; Bashawri, Essam Abdullaziz; Hadidi, Hattan Talal Hassan; Junaid , Ramzy Moaabir Abdu; Alhazmi, Khaled Mala Ali (Journal of Ecohumanism, 2024)
This comprehensive review evaluates the impact of Saudi Vision 2030 on healthcare investments, focusing on the progress, achievements, and challenges in the healthcare sector. Saudi Vision 2030, a transformative national strategy, aims to diversify the economy and improve key sectors, with healthcare as a major focus. The review examines the core objectives of Vision 2030 in healthcare, including infrastructure expansion, workforce development, digital health integration, and research advancements. Key accomplishments are highlighted, such as enhanced healthcare infrastructure, increased healthcare workforce capacity, and advancements in digital health. However, challenges remain in areas like funding allocation, regulatory barriers, and adapting to rapidly evolving technologies. By comparing Saudi Arabia’s healthcare transformation efforts with global standards, this review identifies critical success factors and offers recommendations for sustaining healthcare improvements. The findings underscore the potential for Vision 2030 to significantly impact public health outcomes, quality of care, and healthcare accessibility, ultimately contributing to a modernized, patient-centered healthcare system in Saudi Arabia.